Mobility Studies of 14C-Chlorpyrifos in Malaysian Oil Palm Soils - Nashriyah, Mat; Halimah, Muhamad; Ismail, B. Sahid (Springer New York LLC, 2016)
The mobility of 14C-chlorpyrifos using soil TLC was investigated in this study. It was found that chlorpyrifos was not mobile in clay, clay loam and peat soil. The mobility of 14C-chlorpyrifos and non-labelled chlorpyrifos was also tested with silica gel TLC using three types of developing solvent hexane (100 %), hexane:ethyl acetate (95:5, v/v); and hexane:ethyl acetate (98:2, v/v). The study showed that both the 14C-labelled and non-labelled chlorpyrifos have the same Retardation Factor (Rf) for different developing solvent systems. From the soil column study on mobility of chlorpyrifos, it was observed that no chlorpyrifos residue was found below 5 cm depth in three types of soil at simulation rainfall of 20, 50 and 100 mm. Therefore, the soil column and TLC studies have shown similar findings in the mobility of chlorpyrifos.